2016
DOI: 10.5935/1806-0013.20160011
|View full text |Cite
|
Sign up to set email alerts
|

Does abdominal diastasis influence lumbar pain during gestation?

Abstract: BACKGROUND AND OBJECTIVES:To evaluate and compare the presence and size of recti abdominis diastasis in the second and third gestational trimester and to correlate them to lumbar pain incidence and intensity. METHODS: This is a cross-sectional observational study with 128 pregnant women divided in two groups: 53 pregnant women in the second gestational trimester and 75 pregnant women in the third gestational trimester. Lumbar pain was evaluated with Roland Morris questionnaire and Pain Visual Analog Scale. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
1
0
5
Order By: Relevance
“…Enquanto no GP, os valores mínimos e máximos da PI max foram de -18 e -67 cmH 2 oriundas da gestação, como por exemplo, a redução da força muscular respiratória. Sugere-se seguimento do estudo para obtenção de maior amostragem, o que possibilitará estabelecer valores de referência da força muscular respiratória, da força de preensão palmar e da capacidade funcional para as puérperas.…”
Section: Resultsunclassified
“…Enquanto no GP, os valores mínimos e máximos da PI max foram de -18 e -67 cmH 2 oriundas da gestação, como por exemplo, a redução da força muscular respiratória. Sugere-se seguimento do estudo para obtenção de maior amostragem, o que possibilitará estabelecer valores de referência da força muscular respiratória, da força de preensão palmar e da capacidade funcional para as puérperas.…”
Section: Resultsunclassified
“…It was reported that pain intensity was associated with RAD size and gestational trimester [ 28 ]. However, the current ICD coding mechanisms do not offer details of the data points.…”
Section: Discussionmentioning
confidence: 99%
“…Este processo de retorno estará intensamente associado às transformações gestacionais experimentadas [22]. A dor lombar certamente é uma das mais comuns no período gestacional e parece se agravar no terceiro trimestre [23].…”
Section: Discussionunclassified